Analisis Suseptibilitas Magnetik Tanah dan Laju Evapotranspirasi di Desa Ranooha, Kecamatan Ranomeeto, Kabupaten Konawe Selatan - Khairani, Miftah; Eso, Rosliana; Safiuddin, La Ode (Jurnal Penelitian Pendidikan Fisika, 2020)
The problem in this research is how the magnetic susceptibility of the soil and the rate of evapotranspiration in Ranooha Village, Ranomeeto District, Konawe Selatan District. Soil magnetic susceptibility was measured using Bartington Susceptibility MS2B meter while evapotranspiration rate was measured using Lycimeter. Soil magnetic susceptibility analyzed consisted of three sampling points, each consisting of vegetation (grass) and non-vegetation (without grass) sites, with the same depth variations namely 0 cm, 10 cm, 20 cm, 30 cm, 40 cm and 50 cm. Each sample is coded V00, V10, V20, V30, V40, V50 for sampling at vegetation (grass) sites, and NV00, NV10, NV20, NV30, NV40, and NV50 for sampling at non-vegetation (without grass) sites. The measurement results show that variations in values of Ï‡LF range from a minimum value of 0.8 x 10-8 m3/ kg toa maximum value of 3.8 x 10-8 m3/ kg at point 1, minimum value of 0.8 x 10-8 m3/ kg up to a maximum value of 3.9 x 10-8 m3/ kg at point 2, and a minimum value of 0.9 x 10-8 m3/ kg up to a maximum value of 2.6 x 10-8 m3/ kg at point 3 for vegetation (grass). While variations in values of Ï‡LF rangefrom a minimum value of 1.7 x 10-8 m3/ kg to a maximum value of 2.4 x 10-8 m3/ kg at point 1, a minimum value of 1.6 x 10-8 m3/ kg up to a maximum value of 2.9 x 10-8 m3/ kg at point 2, and a minimum value of 1.6 x 10-8 m3/ kg up to a maximum value of 2.9 x 10-8 m3/ kg at point 3 for non vegetation (without grass). While the maximum rate of evapotranspiration occurs in November for 2018 which is 5.3 mm / day, while the maximum rate of evapotranspiration in 2019 also occurs in November which is 6.1 mm / day for vegetation (grass) sites. While the maximum rate of evapotranspiration occurs in October for 2018 which is 4.3 mm / day, while the maximum rate of evapotranspiration in 2019 occurs in November which is 5.7 mm / day for non-vegetation (without grass) Â sites